2020
DOI: 10.1371/journal.pone.0241816
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of in-hospital cardiac arrest with sequential deployment of rapid response team and medical emergency team to the emergency department and acute care wards

Abstract: Purpose This study aimed to determine if sequential deployment of a nurse-led Rapid Response Team (RRT) and an intensivist-led Medical Emergency Team (MET) for critically ill patients in the Emergency Department (ED) and acute care wards improved hospital-wide cardiac arrest rates. Methods In this single-center, retrospective observational cohort study, we compared the cardiac arrest rates per 1000 patient-days during two time periods. Our hospital instituted a nurse-led RRT in 2012 and added an intensivist-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
2
14
0
4
Order By: Relevance
“…Jones et al confirmed that the RRT reduces the rate of cardiac arrest and reported that one cardiac arrest could be prevented in every 17 by RRT [ 29 ]. The study found the rate of cardiac arrest decreased from 72.62 to 39.01%, which consistent with others [ 14 , 22 , 23 , 27 , 28 ]. These findings may be related to the activation criteria that can be monitored in real time, which can guide callers in identifying high-risk patients early and activate the nurse-led RRS for intervention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Jones et al confirmed that the RRT reduces the rate of cardiac arrest and reported that one cardiac arrest could be prevented in every 17 by RRT [ 29 ]. The study found the rate of cardiac arrest decreased from 72.62 to 39.01%, which consistent with others [ 14 , 22 , 23 , 27 , 28 ]. These findings may be related to the activation criteria that can be monitored in real time, which can guide callers in identifying high-risk patients early and activate the nurse-led RRS for intervention.…”
Section: Discussionsupporting
confidence: 91%
“…RRTs were first launched as a medical emergency team in Australia in the early 1990s. RRTs are now considered by some Western countries as an integral part of hospitals because of the cumulative effect of reducing hospital mortality and cardiac arrest [ 12 – 14 ]. The RRT is made up of multidisciplinary professionals such as critical care nurses, respiratory therapists, and physicians; nurses play a key role in RRT, and most RRS are led by physicians [ 11 , 13 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of CA described in our study was comparable to that in other studies focusing on CA in ED. 9,10 We did not nd data on unex-CAED from other centres for comparison. Our analysis showed that patients with unex-CAED did not differ from patients with expected CA (according to our de nition) in terms of age, sex, and known comorbidities.…”
Section: Discussionmentioning
confidence: 96%
“…Estudo realizado em instituição de saúde norte americana evidenciou que pacientes que receberam o atendimento de suporte básico de vida em cardiologia por protocolo do TRR gerenciado por enfermeiros obtinham 2,5 vezes mais chance de sobrevivência quando comparados aos que não fizeram. As paradas cardíacas em todo o hospital diminuíram de 2,2 eventos por 1.000 pacientes-dia no período anterior a implantação do TRR para 0,8 evento por 1.000 pacientes-dia no período após implantação do serviço (valor p = 0,001), que endossam a terapia inicial avançada do atendimento por enfermeiros (Mankidy, et al, 2020), pois estes permanecem por mais tempo ao lado dos pacientes, com cuidados nas 24 horas nas unidades não críticas, o que desencadeia uma determinante importante nos resultados finais da taxa de sobrevida (Silva, et al, 2021).…”
Section: Discussionunclassified